2014
DOI: 10.1038/ncomms6636
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oceanic-scale interactions on the seasonal modulation of ocean dynamics by the atmosphere

Abstract: Ocean eddies (with a size of 100–300 km), ubiquitous in satellite observations, are known to represent about 80% of the total ocean kinetic energy. Recent studies have pointed out the unexpected role of smaller oceanic structures (with 1–50 km scales) in generating and sustaining these eddies. The interpretation proposed so far invokes the internal instability resulting from the large-scale interaction between upper and interior oceanic layers. Here we show, using a new high-resolution simulation of the realis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

57
301
10

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(395 citation statements)
references
References 40 publications
(73 reference statements)
57
301
10
Order By: Relevance
“…This offers a higher degree of granularity than recent studies that have analyzed bulk seasonal differences in flow characteristics, which are then used to infer submesoscale activity. Both numerical models (Mensa et al 2013;Sasaki et al 2014) and observations (Callies et al 2015;Swart et al 2015;Buckingham et al 2016) provide strong evidence that there are seasonal modulations in submesoscale activity. In general, these reflect a steepening of the kinetic energy spectra during summer, typically with slopes around k…”
Section: Introductionmentioning
confidence: 99%
“…This offers a higher degree of granularity than recent studies that have analyzed bulk seasonal differences in flow characteristics, which are then used to infer submesoscale activity. Both numerical models (Mensa et al 2013;Sasaki et al 2014) and observations (Callies et al 2015;Swart et al 2015;Buckingham et al 2016) provide strong evidence that there are seasonal modulations in submesoscale activity. In general, these reflect a steepening of the kinetic energy spectra during summer, typically with slopes around k…”
Section: Introductionmentioning
confidence: 99%
“…The wind variations thus act as a "pace maker" for the quasi-decadal KE variability by triggering its regime transition (Taguchi et al 2007). Meanwhile, modulated mesoscale eddy activity can lead to modulations in sub-mesoscale streamers and associated vertical motion (Sasaki et al 2014). …”
mentioning
confidence: 99%
“…If baroclinic meanders of scale of approximately 12R d in our experiments can be considered as an analogue of oceanic mesoscale eddies (typically 100-300 km in horizontal extent), the smaller scale filaments and cyclonic eddies in the laboratory flows can be qualified as submesoscale motions. Submesoscale dynamics in the ocean (features of size 1-100 km) has been a subject of a number of recent numerical [e.g., Qiu et al, 2014;Sasaki et al, 2014] and field [e.g., Callies et al, 2015] studies. These studies showed that submesoscale eddy field is quite energetic and can significantly impact the circulation of larger scale.…”
Section: Discussionmentioning
confidence: 99%